Perception of Doctors at Elobied Teaching Hospital Toward Antibiotics Resistance As a Health Threat - Elfaki, AbdelSalam; Elkhider, Mohamed Ali; Ragab, Nosaiba; Eltayeb Yousif Mohammed, Ghorashy (Sudan Journal of Medical Sciences, 2024)
Background: Resistance to antibiotics has increased dramatically over the past few years and has now reached a level that places future patients in real danger. Several factors contribute to this problem, some of them are health workers related and others are community related. This study aimed to assess the awareness of doctors in Elobeid hospital, North Kordofan state, Sudan about the problem, its causes, and its possible preventive measures. Methods: This descriptive, questionnaire-based study was conducted in Elobeid teaching hospital between 2020, February 27 and March 13. The study involved 50 doctors in the internal medicine department. Results: Out of the 50 doctors involved, 49 (98%) agreed that antibiotics resistance is a big progressive health threat in Sudan; 86% of the participants think that selfmedication is the leading cause of antibiotic resistance; and 98% believe that providing good quality culture and sensitivity service in hospitals and health centers is the most effective preventive measure. Regarding education about antibiotics as a part of academic activities in the unit during the last year, 36% of the participants received zero sessions, 68% received 1–5 sessions, and 12% received more than 5 sessions. The assessment of doctor’s adherence to the Sudan Standard Treatment Guideline revealed that 28/50 participants (56%) did not see it or hear about it, 17/50 participants (34%) know it but don’t comply, and only 5/50 participants (10%) know it and comply with it. Conclusion: Participants show a good awareness about the significance of antibiotics resistance as a health threat, a good awareness about the main causes and the possible preventive measures, a low to moderate frequency of education on antibiotics, and a very poor adherence to the Sudan Standard Treatment Guidelines.